2017
DOI: 10.1021/acs.chemrev.7b00259
|View full text |Cite
|
Sign up to set email alerts
|

How Water’s Properties Are Encoded in Its Molecular Structure and Energies

Abstract: How are water’s material properties encoded within the structure of the water molecule? This is pertinent to understanding Earth’s living systems, its materials, its geochemistry and geophysics, and a broad spectrum of its industrial chemistry. Water has distinctive liquid and solid properties: It is highly cohesive. It has volumetric anomalies—water’s solid (ice) floats on its liquid; pressure can melt the solid rather than freezing the liquid; heating can shrink the liquid. It has more solid phases than othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
285
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(321 citation statements)
references
References 400 publications
(702 reference statements)
2
285
0
3
Order By: Relevance
“…[6] Furthermore,asindustry looks to greener processes,there is astrong drive to move away from harsh chemical treatments towards milder and often biotechnologically driven advances that encourage the use of aqueous solvents. [7][8][9][10] Water is also the solvent of choice for biological systems, [10] where exquisite control of reactivity has been demonstrated in complex reaction mixtures. [11,12] If we seek to emulate this level of complexity we must acknowledge,u nderstand and eventually exploit the physical properties of water that make it unique from most other solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Furthermore,asindustry looks to greener processes,there is astrong drive to move away from harsh chemical treatments towards milder and often biotechnologically driven advances that encourage the use of aqueous solvents. [7][8][9][10] Water is also the solvent of choice for biological systems, [10] where exquisite control of reactivity has been demonstrated in complex reaction mixtures. [11,12] If we seek to emulate this level of complexity we must acknowledge,u nderstand and eventually exploit the physical properties of water that make it unique from most other solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction between diphenylurea and poly 1 is a spontaneous adsorption event with a negative Δ S value, so it is less likely for the Δ H to be greater than 0. In fact, the theoretical calculation for the association between 1 and diphenylurea gave a constant Δ H irrespective of the temperature (Table S6), which indicates that a simple mode of association cannot explain the biphasic plot; therefore, the deviation from the Arrhenius‐type plot in Figure may be primarily brought about by temperature‐dependent solvation, which can cause a significant change in Δ S (dashed line in Figure ). Indeed, the microscopic analysis showed that the mean diameter of poly 1 at higher temperatures is significantly larger than that at lower temperatures (Figure S16 and Table S7), and the swelling indicates solvation of the surfaces on poly 1 .…”
Section: Figurementioning
confidence: 99%
“…Classical water force fields (FFs) play central roles in computer molecular modeling as many chemical and biophysical processes happen in aqueous solutions . Depending on whether or not the polarization effect is explicitly considered, most water FFs can be divided into two classes.…”
Section: Introductionmentioning
confidence: 99%
“…As the polarization effect is highly environmental dependent, it is highly realized that the fixed‐charge models fitting only to bulk water properties are not well suited for solutions especially for highly charged biological molecules . The AMOEBA is one of the popular polarizable FFs, where many‐body effects are explicitly taken into account via a linear polarization supposition that can closely reproduce the high‐level quantum potential energy surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation